The power of multi-matrix monitoring in the Pan-Arctic region: plastics in water and sediment - Martin, Jake; Granberg, Maria E.; Provencher, Jennifer; Liborion, Max; Pijogge, Liz; Magnusson, Kerstin; Hallanger, Ingeborg G.; Bergmann, Melanie; Aliani, Stefano; Gomiero, Alessio; Grøsvik, Bjørn Einar; Vermaire, Jesse; et al. (Arctic Science, 2022)
Litter and microplastic assessments are being carried out worldwide. Arctic ecosystems are no exception and plastic pollution is high on the Arctic Council’s agenda. Water and sediment have been identified as two of the priority compartments for monitoring plastics under the Arctic Monitoring and Assessment Programme (AMAP). Recommendations for monitoring both compartments are presented in this publication. Alone, such samples can provide information on presence, fate, and potential impacts to ecosystems. Together, the quantification of microplastics in sediment and water from the same region produce a three-dimensional picture of plastics, not only a snapshot of floating or buoyant plastics in the surface water or water column but also a picture of the plastics reaching the shoreline or benthic sediments, in lakes, rivers, and the ocean. Assessment methodologies must be adapted to the ecosystems of interest to generate reliable data. In its current form, published data on plastic pollution in the Arctic is sporadic and collected using a wide spectrum of methods which limits the extent to which data can be compared. A harmonised and coordinated effort is needed to gather data on plastic pollution for the Pan-Arctic. Such information will aid in identifying priority regions and focusing mitigation efforts.